The performance of lab scale DHS (down-flow hanging sponge) reactor system with activated sludge for raw water treatment - Agung P, Gigih
Water pollution in Indonesia has occurred across many regions. Decentralized treatment is needed to reach smaller towns and villages to ensure the quality of municipal sewage effluent. Among many wastewater treatment system, down-flow hanging sponge (DHS) has been used in many developing countries as cheap and efficient treatment system of sewage. This research aims to assess the performance of lab scale DHS reactor with trickling filter model. Simulation of raw sewage treatment using DHS will involve bioaugmentation of polyurethane foam (PUF) using activated sludge. The capability of biological processes to treat sewage will be compared to sponge adsorption by using new PUF as filter media. The reactor will be operated at hydraulic retention time of 2 and 4 hours by recirculating the effluent back into the DHS filter. BOD, ammonia, nitrite, nitrate, TSS, and total coliform in the wastewater will be calculated during the end of each HRTs. The experiment at 4 hours HRT show that active DHS can reduce 71.14% BOD, 73.30% ammonia, and 77.21% TSS. The capability of DHS in processing wastewater organic content doubled when it is active. Nitrite and nitrate only declined through PUF adsorption, and therefore no nitrite oxidation or denitrification process is observed. In 2 hours, total coliform count has been reduced by 74.19%. Overall, this lab scale DHS operation can be used to improve future pilot scale DHS.